2011
DOI: 10.1016/j.biopsych.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Cues Drive Opposing Context-Dependent Shifts in Reward Processing and Emotional State

Abstract: Background-Prominent neurobiological theories of addiction posit a central role for aberrant mesolimbic dopamine release, but disagree as to whether repeated drug experience blunts or enhances this system. While drug withdrawal diminishes dopamine release, drug sensitization augments mesolimbic function, and both processes have been linked to drug-seeking. One possibility is that the dopamine system can rapidly switch from dampened to enhanced release depending upon the specific drug-predictive environment. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(162 citation statements)
references
References 47 publications
12
149
0
1
Order By: Relevance
“…In general, these substances are readily consumed by mice and rats and elicit appetitive orofacial reactions if infused intraorally, suggesting a positive hedonic evaluation [28,29]. Moreover, mice and rats show increased dopamine efflux and dopamine release in response to free consumption or intraoral delivery of nonnutritive sweeteners [22,30,31]. However, the extent to which these non-nutritive compounds participate in reinforcement/conditioning and how they interact with dopamine signalling during these processes is less clear.…”
Section: Artificial Sweetenersmentioning
confidence: 99%
“…In general, these substances are readily consumed by mice and rats and elicit appetitive orofacial reactions if infused intraorally, suggesting a positive hedonic evaluation [28,29]. Moreover, mice and rats show increased dopamine efflux and dopamine release in response to free consumption or intraoral delivery of nonnutritive sweeteners [22,30,31]. However, the extent to which these non-nutritive compounds participate in reinforcement/conditioning and how they interact with dopamine signalling during these processes is less clear.…”
Section: Artificial Sweetenersmentioning
confidence: 99%
“…For example, both unconditioned rewarding and aversive stimuli increase DA in the NAc shell (Kalivas and Duffy, 1995;Ikemoto, 2007), and this increase is associated with aspects of both approach and avoidance behaviors (Ikemoto and Panksepp, 1999;Di Chiara and Bassareo, 2007;Oleson et al, 2012). Thus, while aversive chemical stimuli have been shown to decrease DA transmission in the NAc shell (Roitman et al, 2008;Wheeler et al, 2011), there are many conditions in which DA release in the NAc shell is critical for the attribution of motivational salience to unconditioned salient stimuli regardless of the valence (Kelley and Berridge, 2002). While recent data have demonstrated that different subsets of DA containing neurons within the VTA are activated by rewarding versus aversive stimuli (Brischoux et al, 2009;Matsumoto and Hikosaka, 2009;Bromberg-Martin et al, 2010;Lammel et al, 2011), it has yet to be determined how this may be associated with social incentives.…”
Section: Pair Bond Maintenance Is Mediated By -Opioid Receptors In Thmentioning
confidence: 99%
“…The present data strengthen a dopamine-suppressive action of aversive stimuli that is consistent with investigations of discrete stimuli in awake and behaving subjects. These studies utilize electrophysiological and electrochemical recordings to demonstrate pauses in dopamine neuron firing (Cohen et al, 2012;Matsumoto and Hikosaka, 2009;Mirenowicz and Schultz, 1996) and dopamine release (Badrinarayan et al, 2012;Roitman et al, 2008;Wheeler et al, 2011) in the NAc following discrete aversive stimuli. Our work extends these findings to include a dopamine-suppressive action of an agent, LiCl, which produces a long-lasting aversive state Tomasiewicz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Discrete aversive stimuli evoke pauses in the firing rate of a clear majority of dopamine neurons (Cohen et al, 2012;Matsumoto and Hikosaka, 2009;Mirenowicz and Schultz, 1996) and suppress phasic dopamine release in the NAc (Badrinarayan et al, 2012;Oleson et al, 2012;Roitman et al, 2008;Wheeler et al, 2011; but also see Anstrom et al, 2009;Brischoux et al, 2009;Budygin et al, 2012;Park et al, 2015 for reported increases in phasic dopamine activity to aversive stimuli under some conditions). However, while discrete stimuli are commonly used to study phasic dopamine responses, the time domain of aversive stimuli can range from discrete to prolonged.…”
Section: Introductionmentioning
confidence: 99%